2021
DOI: 10.1097/hco.0000000000000892
|View full text |Cite
|
Sign up to set email alerts
|

Permission to prescribe: do cardiologists need permission to prescribe diabetes medications that afford cardiovascular benefit?

Abstract: Purpose of reviewAntihyperglycemic therapies including sodium glucose contransporter-2 inhibitors (SGLT2i) and glucagonlike peptide-1 receptor agonists (GLP-1 RA) have been demonstrated to confer significant cardiovascular benefit and reduce future events in patients with type 2 diabetes mellitus (T2DM). However, despite positive data from cardiovascular outcome trials, these therapies remain underutilized in a large proportion of patients who have clinical indications and meet coverage guidelines for their in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
0
6
0
1
Order By: Relevance
“…Additionally, while we used metformin prescriptions as a surrogate for patients being actively managed for type 2 diabetes, the use of metformin for other indications, including prediabetes and polycystic ovarian syndrome, may be reflected in modest reductions in the observed use of SGLT2i and GLP1-RA as compared to metformin. However, the vast majority of metformin use is for patients with established type 2 diabetes as less than 1% of those with prediabetes are prescribed metformin and it is no longer strongly recommended for polycystic ovarian syndrome, and is therefore, unlikely to substantially affect our observations [ 37 , [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ]. Finally, identifying counties based on city and state is slightly imprecise given variations in how administrative divisions are defined (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, while we used metformin prescriptions as a surrogate for patients being actively managed for type 2 diabetes, the use of metformin for other indications, including prediabetes and polycystic ovarian syndrome, may be reflected in modest reductions in the observed use of SGLT2i and GLP1-RA as compared to metformin. However, the vast majority of metformin use is for patients with established type 2 diabetes as less than 1% of those with prediabetes are prescribed metformin and it is no longer strongly recommended for polycystic ovarian syndrome, and is therefore, unlikely to substantially affect our observations [ 37 , [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ]. Finally, identifying counties based on city and state is slightly imprecise given variations in how administrative divisions are defined (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…22 Uvedená nerozhodnost a váhavost byla ostatně pozorována i při zavádění nových antidiabetik u pacientů s diabetem 2. typu (T2DM) a s prokázaným aterosklerotickým kardiovaskulárním onemocněním. 23 Jedná se o nesmírně důležitou otázku, protože: 1) optimální léčby se nedostává vysokému procentu vhodných pacientů, a 2) pokud se již u nich provádí, zahájení léčby se často dlouho odkládá. Souhrnné údaje ze studií ukazují, že přínos optimální léčby se již brzy po jejím zahájení zvyšuje; proto neprovádění optimální léčby, nebo dokonce její oddalování vystavuje pacienty riziku, které lze potenciálně odvrátit.…”
Section: Zkratky a Akronymyunclassified
“…Although there is strong evidence to initiate these medications in both diabetes and nondiabetes populations, there is therapeutic inertia among nonendocrine providers [28 ▪ ]. A global prospective observational study known as DISCOVER, followed >14 000 patients with type 2 diabetes from 37 countries over 3 years [29].…”
Section: Reviewmentioning
confidence: 99%
“…They found that 1579 patients (10.8%) were started on an SGLT-2i (1275; 8.7%) or GLP-1 RA (318; 2.2%) at enrollment, increasing to 2348 patients (16.1%) for either agent (1870 [12.8%] SGLT-2i only, 376 [2.6%] GLP-1 RA only, 102 [0.7%] both agents) at the end of the study [29].Although the use increased over time, it was still suboptimal for the desired population. Barriers to prescribing these cardioprotective agents include reluctance to overstep interdisciplinary boundaries, medication side effects, unfamiliarity, and discomfort with choosing the correct agent in the evolving type 2 diabetes pharmacotherapeutic field [28 ▪ ].…”
Section: Reviewmentioning
confidence: 99%